Indonesian Translation of Articles about Memory and Study Skill - Luthvia Luthvia; Dini Kurnia Irmawati (Jurnal VOK@SINDO, 2015)
Many modern learning media that is up to date nowadays, one of them is online learning media. Online learning media is a learning medium which is practical without needing face to face method and the user need to choose the material topic that they want to learn and must follow the curriculum step by step. Unfortunately, it is less interested by Indonesian citizen because there is no produsen who provides this medium. So that, kerja.id comes up with solution for them who want to excell their grade and want to learn simply. One of the main topics in kerja.id is “Memory and Study Skill”. This article is important topic to be discuused for youth people especially for students or they who want to prepare in applying job and worker who want to upgrade their quality of work. Due to many jobless people and the decreasing number of good quality students, this article is the best solution to increase nation students learning quality and decrease the number of jobless in this country. The translating result of this article can make the readers especially students easily to understand the material about how to be succes student with a new easy way and guaranteed result. This article also completed by steps to achieve the goal that they want.